Schistosoma japonicum Infection Promotes the Response of Tfh Cells Through Down-Regulation of Caspase-3–Mediating Apoptosis - Yang, Quan; Qu, Jiale; Jin, Chenxi; Feng, Yuanfa; Xie, Shihao; Zhu, Jinxin; Liu, Gaoshen; Xie, Hongyan; Qiu, Huaina; Qi, Yanwei; Mu, Jianbing; Huang, Jun (Frontiers in Immunology, 2019)
CD4+ T follicular helper (Tfh) cells, a new subset of immune cells, have been demonstrated to be involved in granulomatous responses to Schistosoma japonicum (S. japonicum) infection. However, their role and the detailed mechanisms of Tfh cell aggregation remain to be described. In this study, we provide evidence that S. japonicum infection enhances the accumulation of Tfh cells in the spleen, lymph nodes, and peripheral blood of C57BL/6 mice. Infection-induced Tfh cells have a more potent facilitated effect directly on B-cell responses than do control Tfh cells (P<0.05). Furthermore, reduced apoptosis of Tfh cells was found both in S. japonicum–infected mice and in cultured Tfh cells treated with soluble egg antigen (SEA) (P<0.05). Mechanistic studies revealed that caspase-3 signal mediated SEA-induced down-regulated apoptosis. In summary, this study demonstrates that Tfh cell accumulation might mediate the effects of S. japonicum infection on the immune system, and sheds new light on the mechanism of Tfh cells accumulation.